Affine Poisson Groups and WZW Model - Klimcík, C. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We give a detailed description of a dynamical system which enjoys a Poisson-Lie symmetry with two non-isomorphic dual groups. The system is obtained by taking the q → ∞ limit of the q-deformed WZW model and the understanding of its symmetry structure results in uncovering an interesting duality of its exchange relations.